Transforming Growth Factor-β1 Promotes M1 Alveolar Macrophage Polarization in Acute Lung Injury by Up-Regulating DNMT1 to Mediate the microRNA-124/PELI1/IRF5 Axis - Wang, Yongqi; Wang, Xiaoqing; Zhang, Hong; Han, Biao; Ye, Yuanmei; Zhang, Mengjie; Wang, Yingbin; Xue, Jianjun; Wang, Chun’ai (Frontiers in Cellular and Infection Microbiology, 2021)
Objective Macrophages function as key orchestrators in the pathogenesis of acute lung injury (ALI). The current study sets out to investigate the molecular mechanism of transforming growth factor-β (TGFβ1) in the regulation of M1 alveolar macrophage polarization in ALI by modulating DNA methyltransferase 1 (DNMT1), along with the microRNA (miR)-124/Pellino 1 (PELI1)/interferon regulatory factor 5 (IRF5) axis. Methods First, ALI mouse models were established, and the proportion of M1 and M2 macrophages in mouse lung tissues was detected using flow cytometry. The targeting relationship between miR-124 and PELI1 was verified with the help of a dual luciferase gene reporter assay. Following TGFβ1 knockdown, RT-qPCR and Western blot assay were performed to analyze the expression patterns of TGFβ1, DNMT1, miR-124, and PELI1 and M1/M2 polarization markers in the lung tissues of ALI mice. Immunofluorescence was further employed to detect nuclear translocation of IRF5 in macrophages. Results The polarization of M1 macrophages was found to be positively correlated with the severity of lung injury. TGFβ1, DNMT1, PELI1 were highly expressed, while miR-124 was down-regulated in ALI mice, and IRF5 was primarily distributed in the nucleus. TGFβ1 promoted the polarization of M1 alveolar macrophages by up-regulating DNMT1. Furthermore, DNMT1 down-regulated the expression of miR-124, which led to enhancement of M1 alveolar macrophage polarization. Meanwhile, over-expression of miR-124 inhibited the nuclear translocation of IRF5 and suppressed M1 alveolar macrophage polarization. On the other hand, over-expression of PELI1 reversed the above trends. Conclusion Collectively, our findings indicated that TGFβ1 can promote the expression of DNMT1, which down-regulates miR-124 to activate PELI1 and nuclear translocation of IRF5, thereby aggravating ALI in mice.